Organizational cloud security and control: a proactive approach. Issue 3 (3rd June 2019) - Spanaki, Konstantina; Gürgüç, Zeynep; Mulligan, Catherine; Lupu, Emil
Abstract : Purpose: The purpose of this paper is to unfold the perceptions around additional security in cloud environments by highlighting the importance of controlling mechanisms as an approach to the ethical use of the systems. The study focuses on the effects of the controlling mechanisms in maintaining an overall secure position for the cloud and the mediating role of the ethical behavior in this relationship. Design/methodology/approach: A case study was conducted, examining the adoption of managed cloud security services as a means of control, as well as a large-scale survey with the views of IT decision makers about the effects of such adoption to the overall cloud security. Findings: The findings indicate that there is indeed a positive relationship between the adoption of controlling mechanisms and the maintenance of overall cloud security, which increases when the users follow an ethical behavior in the use of the cloud. A framework based on the findings is built suggesting a research agenda for the future and a conceptualization of the field. Research limitations/implications: One of the major limitations of the study is the fact that the data collection was based on the perceptions of IT decision makers from a cross-section of industries; however the proposed framework should also be examined in industry-specific context. Although the firm size was indicated as a high influencing factor, it was not considered for this study, as the data collection targeted a range of organizations from various sizes. Originality/value: This study extends the research of IS security behavior based on the notion that individuals (clients and providers of cloud infrastructure) are protecting something separate from themselves, in a cloud-based environment, sharing responsibility and trust with their peers. The organization in this context is focusing on managed security solutions as a proactive measurement to preserve cloud security in cloud environments.